2021
DOI: 10.3390/ijerph19010242
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Clinical Trial of a Mouthwash Containing Glycyrrhiza uralensis Extract for Preventing Dental Caries

Abstract: This study sought to confirm the effect of using a mouthwash containing Glycyrrhiza uralensis extract for oral health management by investigating changes in the pH of dental plaque and bacteria that cause dental caries. A randomized, double-blind, placebo-controlled study was conducted on 60 subjects categorized in either the Glycyrrhiza uralensis extract gargle group (n = 30) or the saline gargle group (n = 30). Scaling was conducted in order to ensure the homogeneity of the oral environment, while gargling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Moreover, licorice extract has antimicrobial effects on bacterial pathogens, such as S. aureus [38] and Streptococcus mutans, a main oral pathogen causing dental caries [39]. In a clinical trial, mouthwash containing licorice extract inhibited oral pathogens effectively [40]. The findings in this study suggest that licorice extract can possibly be used as a drug potentiator to improve the efficacy of antimicrobial therapy for treating listeriosis.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, licorice extract has antimicrobial effects on bacterial pathogens, such as S. aureus [38] and Streptococcus mutans, a main oral pathogen causing dental caries [39]. In a clinical trial, mouthwash containing licorice extract inhibited oral pathogens effectively [40]. The findings in this study suggest that licorice extract can possibly be used as a drug potentiator to improve the efficacy of antimicrobial therapy for treating listeriosis.…”
Section: Discussionmentioning
confidence: 68%
“…The mouthwash also showed excellent effect of inhibiting bacteria that cause dental caries. Compared to dental clinical studies on Glycyrrhiza uralensis extract 17 and Sambucus williamsii var. coreana extract 18 for S. mutans, which are the most common cause of dental caries, S. mutans was not detected at all in the mandibular from immediately after gargle of Lespedeza cuneate extract used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dental clinical research is being conducted to evaluate the effect of using mouthwash containing natural substances on preventing dental caries. It was found that a mouthwash containing Glycyrrhiza uralensis extract can prevent dental caries and also lower the risk of dental caries 17 . In addition, a study by Kim and Nam reported that a natural mouthwash containing Sambucus williamsii var.…”
mentioning
confidence: 99%
“…In addition, there are plenty of oral non-developmental problems associated with MMP production and activity. Dental caries is a prominent multifactorial condition affecting the teeth, caused directly by microorganisms [ 95 , 96 , 97 ]. It is a progressive destruction of hard tooth tissues (enamel and dentine), involving demineralization of the inorganic parts as well dissolution of the organic components [ 98 ].…”
Section: A Brief Glance At the Role Of Matrix Metalloproteinases In T...mentioning
confidence: 99%